Gingival landmarks and cutting points for gingival phenotype determination: A clinical and tomographic cross-sectional study - Rodrigues, Diogo Moreira; Petersen, Rodrigo Lima; de Moraes, José Rodrigo; Barboza, Eliane Porto (Journal of periodontology (1970), 2022)
This cross-sectional study assessed the role of gingival landmarks (GLs) and cutting points (CPs) for gingival phenotype (GP) determination. Six maxillary anterior teeth (70 subjects) were evaluated using soft tissue cone-beam computed tomography (ST-CBCT). Gingival thickness was measured at different GLs: 1) tissue zone (gingival margin [GM], 1 and 2 mm apical to GM, cemento-enamel junction, above the bone crest); 2) bone zone (buccal bone crest [BBC], 1, 2, and 3 mm apical to BBC). CPs of 0.6, 0.8, 1.0, 1.2, and 1.5 mm were used to discriminate between thin and thick GP. The clinical determination of GP was made based on transparency of the periodontal probe (TRAN). The prevalence of thin and thick GP depended on the GL and CP. Considering the CP (1 mm), thin GP at the tissue zone ranged from 99% at the GM to 10.2% above the bone crest. In the bone zone, thick GP ranged from 28% at the BBC to 6% at 3 mm apical to the BBC. The predictability of a correct assessment of GP by TRAN compared with ST-CBCT was influenced by the GLs and CPs. A slight agreement (kappa <0.2) and low accuracy (area under the curve <0.7) were found between methods. The determination of thin and thick GPs is related to the gingival landmarks and CPs. Further studies are required for a well-defined treatment protocol considering different gingival landmarks in tissue and bone zones. An ST-CBCT may be useful for this purpose.